2023
DOI: 10.1001/jamanetworkopen.2023.14848
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Automated Bilingual Digital Health Tool to Reduce Unhealthy Alcohol Use Among Latino Emergency Department Patients

Abstract: ImportanceAlcohol use disorders have a high disease burden among US Latino groups. In this population, health disparities persist, and high-risk drinking has been increasing. Effective bilingual and culturally adapted brief interventions are needed to identify and reduce disease burden.ObjectiveTo compare the effectiveness of an automated bilingual computerized alcohol screening and intervention (AB-CASI) digital health tool with standard care for the reduction of alcohol consumption among US adult Latino emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…It has been reported that patients with limited English language proficiency experience high rates of medical errors and worse clinical outcomes compared with English-speaking patients . The current study by Vaca et al is a leader in introducing problems related to the Latino community and AUDs, but it opens exploration to other potential research topics addressing how the Latino community has been affected by AUDs. Patients with AUDs can have comorbidities, such as cirrhosis, which can eventually develop into hepatocellular carcinoma, for which the treatment is often a liver transplant.…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…It has been reported that patients with limited English language proficiency experience high rates of medical errors and worse clinical outcomes compared with English-speaking patients . The current study by Vaca et al is a leader in introducing problems related to the Latino community and AUDs, but it opens exploration to other potential research topics addressing how the Latino community has been affected by AUDs. Patients with AUDs can have comorbidities, such as cirrhosis, which can eventually develop into hepatocellular carcinoma, for which the treatment is often a liver transplant.…”
mentioning
confidence: 87%
“…The article by Vaca et al provides the results of a randomized clinical trial investigating the use of a bilingual alcohol screening tool vs standard care to reduce high-risk alcohol consumption in Latino ED patients. The authors that found those who received the trial intervention had significantly fewer binge drinking episodes within the last 28 days at 12 months after randomization. In addition, Latino participants more often preferred to use the bilingual tool in the Spanish language.…”
mentioning
confidence: 99%
See 3 more Smart Citations